HEAD OF MADRASAH LEADERSHIP STRATEGIES IN IMPROVING TEACHER PERFORMANCE THROUGH ACADEMIC SUPERVISION AT MTs NEGERI BINJAI - Wan Anwar Fuadi; Muhammad Rifa’i; Neliwati (Pena Cendekia Insani, 2025)
This study aims to describe the leadership strategies of the madrasah principal in improving teacher performance through the implementation of academic supervision at MTs Negeri Binjai. The research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The findings reveal a decline in teacher performance, characterized by poor punctuality, lack of instructional innovation, and insufficient attention to students' needs. The principal applied a humanistic and participative leadership strategy through a structured academic supervision process. These strategies included situational leadership styles, binding and bonding approaches, and collaborative reflection between teachers and leadership. Academic supervision served as a medium for teacher coaching and professional development through direct classroom observations, constructive feedback, and pedagogical dialogue. The results indicate that appropriate leadership strategies and continuous supervision can significantly enhance teachers’ competence and motivation. This study recommends strengthening participatory leadership practices and developing adaptive academic supervision systems as efforts to improve the quality of education in madrasahs.